Urgency Of Fulfilling Sexual Rights For Prisoners Perspective Of The Non-Discrimination Principle - Sihombing, Eka N.A.M.; Hadita, Cynthia (Jurnal Hukum Replik, 2025)
The unfulfilled sexual rights for prisoners cause problems related to potential such as psychological shocks, sexual violence between fellow prisoners, high divorce rates for married prisoners, besides that the absence of sexual rights for prisoners in laws and regulations in Indonesia violates the principle of non-discrimination for prisoners so it needs to be studied in the perspective of human rights, especially sexual rights for prisoners. The method used is normative juridical with a doctrinal approach. The results showed that the urgency of regulations related to sexual rights for prisoners so that there is fulfillment of sexual rights that do not injure the principle of non-discrimination for prisoners so that legal certainty related to sexual rights for prisoners can minimize psychological shocks, sexual violence between fellow prisoners, high divorce rates for married prisoners.Keywords: Rights, Sexual, Prisoner